2020
DOI: 10.18632/aging.102702
|View full text |Cite
|
Sign up to set email alerts
|

Chikusetsu saponin IVa protects pancreatic β cell against intermittent high glucose-induced injury by activating Wnt/β-catenin/TCF7L2 pathway

Abstract: Islet β cell mass reduction induced by glucose fluctuation is crucial for the development and progression of T2DM. Chikusetsu saponin IVa (CHS) had protective effects against DM and related injuries. Here we aimed to investigate the role of CHS in β cell injuries and its possible mechanism involved. Isolated rat islets, βTC3 cells and T2DM mice were used in this study. The results showed that CHS restored the secretion activity, promoted β cell survival by increasing β cell proliferation and decreasing apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…CHS, one triterpenoid saponin with many pharmacological activities, is abundantly found in various medicinal plants, such as Panax japonicus , Aralia taibaiensis , and other plants. In previous studies, we had shown its protective effects against oxidative damage in cardiomyocytes and brain cells, and beneficial effects on intermittent hyperglycemia induced pancreatic islet injuries [ 24 , 31 , 32 ]. However, its effects against lipotoxicity-induced pancreatic islet injuries were largely unknown to us.…”
Section: Discussionmentioning
confidence: 99%
“…CHS, one triterpenoid saponin with many pharmacological activities, is abundantly found in various medicinal plants, such as Panax japonicus , Aralia taibaiensis , and other plants. In previous studies, we had shown its protective effects against oxidative damage in cardiomyocytes and brain cells, and beneficial effects on intermittent hyperglycemia induced pancreatic islet injuries [ 24 , 31 , 32 ]. However, its effects against lipotoxicity-induced pancreatic islet injuries were largely unknown to us.…”
Section: Discussionmentioning
confidence: 99%
“…Several WNT pathways, such as WNT3a/β‐catenin 204–206 and WNT4/PCP, 207 could improve β cell proliferation and insulin secretion. In‐depth dissections revealed that the activation of TCF7L2 and FoxO1 is key to this proproliferation effect of WNT3a/β‐catenin pathway 187,208,209 . TCF7L2 is crucial to maintaining the normal functions of β cells, and its silencing can inhibit GSIS through regulating the expression of genes that control the fusion of secretory granule, such as syntaxin 1A, and syntaxin‐binding protein 1 210 .…”
Section: Signaling Pathways In T2dmmentioning
confidence: 99%
“…The knockout of Wnt10b in vivo leads to an increased potential for the trans-differentiation of myoblasts into adipocytes and the acquisition of adipocyte characteristics during muscle regeneration ( Taylor-Jones et al, 2002 ; Vertino et al, 2005 ). Components of the Wnt pathway are abundantly expressed in the pancreas and tissues of the small intestine, thereby playing a role in the direct or indirect regulation of the functionality of pancreatic β-cells ( Cui et al, 2020 ). In vitro studies have shown that Wnt signaling molecules regulate a variety of cell cycle regulators and then promote the growth and proliferation of islet β-cells ( Rulifson et al, 2007 ; Yoshihara et al, 2020 ).…”
Section: The Wnt Signaling Pathway and Diabetesmentioning
confidence: 99%